2009
DOI: 10.1096/fj.09-139691
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of physical performance and cognitive function in rats with short‐term high‐fat feeding

Abstract: Efficiency, defined as the amount of work produced for a given amount of oxygen consumed, is a key determinant of endurance capacity, and can be altered by metabolic substrate supply, in that fatty acid oxidation is less efficient than glucose oxidation. It is unclear, however, whether consumption of a high-fat diet would be detrimental or beneficial for endurance capacity, due to purported glycogen-sparing properties. In addition, a high-fat diet over several months leads to cognitive impairment. Here, we tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
97
4
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 36 publications
11
97
4
4
Order By: Relevance
“…17,19 However, high-fat diets can also lead to higher levels of mitochondrial uncoupling protein (UCP3), which reduces the efficiency of energy production and, therefore, can impair exercise capacity. 41 Although the precise limitation(s) on endurance exercise performance depend on the intensity and/or duration of the activity, the depletion of energy substrates is a commonly considered cause of fatigue. The ingestion, loading or use of particular dietary macronutrients is important in maintaining muscular activity and delaying fatigue during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…17,19 However, high-fat diets can also lead to higher levels of mitochondrial uncoupling protein (UCP3), which reduces the efficiency of energy production and, therefore, can impair exercise capacity. 41 Although the precise limitation(s) on endurance exercise performance depend on the intensity and/or duration of the activity, the depletion of energy substrates is a commonly considered cause of fatigue. The ingestion, loading or use of particular dietary macronutrients is important in maintaining muscular activity and delaying fatigue during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of a link between food intake and impaired memory performance is accumulating (for a review, see [23]). First, for the case of an overly rich diet, such as the Western diet, it has been shown that feeding rats a high-fat diet alters working memory, even after only 3 [77] or 9 days [110]. This type of memory is impaired both in the short and longterm [77].…”
Section: Hippocampus and Memory For Food Intakementioning
confidence: 99%
“…Diets with high saturated fat content impaired cognitive function in a delayed alternation task in young rats, and the percent of saturated fat in the diet correlated positively with behavioral impairment (61). Murray et al showed that only 9 days of a high-fat diet was sufficient to cause physical impairment on a treadmill and cognitive impairment in the water maze (121). When 16-month-old rats were fed diets high in fat and cholesterol they made more errors in a test of working memory especially when memory loads were high, and they also showed altered hippocampal morphology (60).…”
Section: Animal Studiesmentioning
confidence: 99%